Haemodynamic effects of pharmacologic stress with adenosine in patients with left ventricular systolic dysfunction. (1st March 2019) - Gulsin, Gaurav S.; Abdelaty, Ahmed M.S.E.K.; Shetye, Abhishek; Lai, Florence Y.; Bajaj, Amrita; Das, Indrajeet; Deshpande, Aparna; Rao, Praveen P.G.; Khoo, Jeffrey; McCann, Gerry P.; Arnold, Jayanth R.
Abstract: Background: In patients with heart failure, downregulation of adenosine receptor gene expression and impaired adenosine-related signal transduction may result in a diminished response to adenosine. This may have implications for cardiac stress testing. We evaluated the haemodynamic response to intravenous adenosine in patients with left ventricular systolic dysfunction (LVSD) undergoing stress cardiovascular magnetic resonance imaging (CMR). Methods and results: We retrospectively examined 497 consecutive patients referred for clinical stress CMR. Blood pressure and heart rate responses with intravenous adenosine were compared in patients with normal, mild-moderately impaired and severely impaired LV systolic function (ejection fraction [EF] > 55%, 36–55% and < 35%, respectively). Following 2 min of adenosine infusion, there was a significant difference between the groups in the heart rate change from baseline, with a diminished heart rate response in patients with LVSD ( p < 0.001). An increase in the dose of adenosine (up to 210 μg/kg/min) was required to achieve a sufficient haemodynamic response in more patients with severe LVSD (41%) than those with mild-moderately impaired and normal LV systolic function (24% and 19%, respectively, p < 0.001). Even with increased doses of adenosine in subjects with severe LVSD, peak haemodynamic response remained blunted. With multivariate analysis age ( p < 0.001) and LVEF ( p = 0.031) were independent predictors of heart rate response to adenosine. Conclusion: Patients with reduced LVEF referred for stress CMR may have a blunted heart rate response to adenosine. Further study is warranted to determine whether this may be associated with reduced diagnostic accuracy and also the potential utility of further dose increases or alternative stressors.